Beliefs and attitudes of older adults and carers about deprescribing of medications: a qualitative focus group study - Reeve, Emily (Br J Gen Pract, 2016)
BACKGROUND: Deprescribing describes the complex process that is required for the safe and effective cessation of medications that are likely to cause more harm than benefit. Knowledgeof older adults’ and carers’ attitudes towards deprescribing will enhance shared decision making in medication optimisation. AIM: To explore the views, beliefs, and attitudes of older adults and carers on deprescribing. DESIGN AND SETTING: Qualitative focus group study in New South Wales, Australia. METHOD: Four focus groups with 14 older adults and 14 carers were conducted. Results were analysed using a previously developed framework (directed content analysis) with additional conventional content analysis. RESULTS: The willingness of both older adults and carers to have one or more medications deprescribed was influenced by the following main themes: their perception of the appropriateness of that medication; fear of outcomes of withdrawal; dislike of taking medications; and the availability of a process for withdrawal (including a discussion with a healthcare professional and knowing that the medication could be restarted if necessary). A patient’s regular GP was identified as a strong influence both for and against medication withdrawal. The identified themes supported the previously developed framework. An additional theme unique to the carers was the complexity involved in making decisions about medications for their care recipients. CONCLUSION: This study highlights that discussions between the healthcare professional and the olderadult or carer about withdrawing medications should address reasons for deprescribing. GPs should be aware of their major influence on patients and regularly discuss appropriateness of current medication use with older adults and their carers.